Corrosion-resistant polytetrafluoroethylene pipe and application thereof

By mixing polytetrafluoroethylene with modifier and copolymer, and after extrusion molding and sintering, corrosion-resistant polytetrafluoroethylene pipes with excellent mechanical properties, low dynamic friction coefficient and antibacterial effect are prepared, which solves the shortcomings of polytetrafluoroethylene pipes in the prior art in terms of mechanical strength, thermal stability and antibacterial properties, and is suitable for high-hard application environments in chemical industry, petroleum and other fields.

CN119591997APending Publication Date: 2025-03-11GUANGDONG DECHUANGXIN MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411919613.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing polytetrafluoroethylene pipes have shortcomings in terms of mechanical strength, thermal stability and antibacterial properties, and are difficult to meet the high demanding application environment needs in the fields of chemical industry, petroleum and other fields.

Method used

By mixing polytetrafluoroethylene with perfluorocarboxylate, antibacterial agent, filler, coupling agent and modified acrylate copolymer, and after extrusion molding and sintering, corrosion-resistant polytetrafluoroethylene pipes with excellent mechanical properties, low dynamic friction coefficient and antibacterial effect were prepared.

Benefits of technology

It significantly improves the mechanical properties, antibacterial properties and service life of PTFE pipes, while reducing the dynamic friction coefficient, and is suitable for high-performance pipe needs in chemical, oil and natural gas fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005207627900000081
    Figure BDA0005207627900000081
  • Figure BDA0005207627900000091
    Figure BDA0005207627900000091
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant polytetrafluoroethylene pipe and application thereof. The polytetrafluoroethylene pipe comprises polytetrafluoroethylene, perfluorocarboxylate, a filler, a coupling agent and a modified acrylate copolymer. The modified acrylate copolymer is prepared from a modifier, a flexible monomer, a rigid monomer and a grafting agent, the grafting agent contains double bonds and can react with the modifier, and functional groups are introduced to prepare the modified acrylate copolymer; the polytetrafluoroethylene pipe is prepared through the steps of raw material mixing, extrusion molding, sintering, cooling and the like. The pipe has excellent antibacterial property, mechanical property and self-lubricating property, and is longer in service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polytetrafluoroethylene, in particular to a corrosion-resistant polytetrafluoroethylene pipe and application thereof. Background Art

[0002] As a polymer material with excellent chemical stability, non-stickiness, low friction coefficient and good temperature resistance, polytetrafluoroethylene has been widely used in many fields such as chemical industry, electronics, and medical treatment. Especially in pipeline systems that require high corrosion resistance and non-adhesion, polytetrafluoroethylene pipes are favored due to their unique properties. However, traditional polytetrafluoroethylene pipes have some performance limitations, such as low mechanical strength, hardness, and insufficient dimensional stability under high temperature conditions, which limit their use in more demanding application environments.

[0003] In practical applications, especially in the chemical and petroleum industries, pipes need to have good corrosion resistance, excellent flame retardancy and sufficient mechanical strength. The performance balance of existing PTFE pipes in these aspects still needs to be improved.

[0004] However, they often only improve a specific performance, but fail to comprehensively improve the flame retardancy, heat resistance and mechanical properties of PTFE pipes. In some cases, these modification methods may introduce new problems, such as increased processing complexity, rising costs or short-term modification effects.

[0005] CN113354913A discloses a polytetrafluoroethylene pipe and a preparation method thereof, including; a plasticizer, a reinforcing fiber, and a modified polytetrafluoroethylene; the preparation steps of the modified polytetrafluoroethylene are modification treatment: polytetrafluoroethylene, a modified emulsion and ammonium persulfate are heated and mixed to obtain a mixture; the modified emulsion is composed of glycidyl methacrylate, polypropylene wax, and hexafluorobutyl methacrylate; through grafting treatment: the mixture is mixed with a metal salt, and an electrode is connected, and after the electrical treatment, hexafluoropropylene is pressurized into the polytetrafluoroethylene, and heated for reaction to obtain the modified polytetrafluoroethylene. The polytetrafluoroethylene pipe prepared by the invention has excellent tensile strength and compressive strength. However, the polytetrafluoroethylene pipe prepared by this method has poor thermal stability.

[0006] CN113416369A discloses a modified polytetrafluoroethylene molded pipe and a preparation method thereof, a modified polytetrafluoroethylene molded pipe, comprising the following components in parts by weight: fiber filler; toughening agent; antioxidant; modified polytetrafluoroethylene; the preparation steps of modified polytetrafluoroethylene are as follows: pretreatment: connect polytetrafluoroethylene to an electrode, introduce hydrogen and nitrogen, and pressurize to obtain amino polytetrafluoroethylene; modification treatment: heat and mix amino polytetrafluoroethylene with a mixed resin and a modified filler, and then ultrasonically clean to obtain modified polytetrafluoroethylene; the mixed resin is composed of acrylic resin, polyamide polyamine epichlorohydrin resin and alkyd resin. The modified polytetrafluoroethylene molded pipe prepared by the method has the characteristics of not easy to deform and pull. However, the polytetrafluoroethylene molded pipe prepared by the method has poor heat resistance, is easy to burn in the event of a fire, and is easy to cause an accident. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to improve the antibacterial property and mechanical property of the corrosion-resistant polytetrafluoroethylene pipe and reduce the dynamic friction coefficient to extend the service life of the polytetrafluoroethylene pipe.

[0008] To achieve the above object, the present invention provides a corrosion-resistant polytetrafluoroethylene pipe. The preparation method of the corrosion-resistant polytetrafluoroethylene pipe comprises the following steps, calculated by weight:

[0009] Step 1, 30-50 parts of polytetrafluoroethylene, 2-5 parts of perfluorocarboxylate, 0.5-1 parts of antibacterial agent, 5-20 parts of filler, 1-4 parts of coupling agent and 5-20 parts of modified acrylate copolymer are mixed evenly, and extruded to obtain a molded product;

[0010] Step 2: sinter the formed product at 310-390° C., and cool the sintered product at room temperature to obtain a polytetrafluoroethylene tube.

[0011] The preparation method of the modified acrylate copolymer comprises the following steps:

[0012] S1, diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, alkaline regulator, modifier, flexible monomer, rigid monomer and grafting agent are uniformly mixed to obtain a monomer mixture, and the monomer mixture is evenly divided into two equal parts for standby use;

[0013] S2, separately stirring water, diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether and alkaline regulator at a constant temperature, then adding one portion of the monomer mixture prepared in step S1, and continuing stirring for 10-50 minutes to obtain a pre-emulsion;

[0014] S3, dissolving ammonium persulfate in water to obtain an ammonium persulfate aqueous solution for standby use;

[0015] S4, adding water to the remaining monomer mixture prepared in step S1, heating to 60-80° C., adding 1 / 4-1 / 2 of the pre-emulsion prepared in step S2 and 1 / 4-1 / 2 of the ammonium persulfate aqueous solution prepared in step S3, raising the temperature to 85-100° C. and maintaining the temperature unchanged, continuing to stir, and continuing to stir after obvious blue light appears to obtain a seed emulsion;

[0016] S5. Continue to add the remaining pre-emulsion and aqueous ammonium persulfate solution to the seed emulsion prepared in step S4 within 2-5 hours, keep warm at 85-100° C. for 1-4 hours, then cool to 30-55° C., adjust the pH with aqueous ammonia, cool to room temperature, filter, dry, and cool to obtain a modified acrylate copolymer.

[0017] More preferably, the preparation method of the modified acrylate copolymer comprises the following steps, in parts by weight:

[0018] S1. Evenly mix 4-15 parts of diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, 2-8 parts of alkaline regulator, 3-15 parts of modifier, 5-14 parts of flexible monomer, 3-16 parts of rigid monomer and 3-15 parts of grafting agent to obtain a monomer mixture, and divide the monomer mixture into two equal parts for standby use;

[0019] S2, 10-50 parts of water, 2-13 parts of diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, and 2-8 parts of sodium carbonate are stirred at a constant temperature, and then one part of the monomer mixture prepared in step S1 is added, and stirring is continued for 20-50 minutes to obtain a pre-emulsion;

[0020] S3, dissolving 2-8 parts of ammonium persulfate in water to obtain an ammonium persulfate aqueous solution for standby use;

[0021] S4, adding 10-50 parts of water to the remaining monomer mixture prepared in step S1, heating to 60-80° C., adding 1 / 4-1 / 2 of the pre-emulsion prepared in step S2 and 1 / 4-1 / 2 of the ammonium persulfate aqueous solution prepared in step S3, raising the temperature to 85-100° C. and maintaining the temperature unchanged, continuing to stir, and continuing to stir after obvious blue light appears to obtain a seed emulsion;

[0022] S5. Continue to add the remaining pre-emulsion and aqueous ammonium persulfate solution to the seed emulsion prepared in step S4 within 2-5 hours, keep warm at 85-100° C. for 1-4 hours, then cool to 30-55° C., adjust the pH with aqueous ammonia, cool to room temperature, filter, dry, and cool to obtain a modified acrylate copolymer.

[0023] Preferably, the modifier is any one of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, di(2-methyl-2-acrylic acid) 2-hydroxy-1,3-propylene glycol ester, and (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate.

[0024] More preferably, the modifier is (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate.

[0025] Preferably, the flexible monomer is octadecyl acrylate; and the rigid monomer is theaflavin-3-gallate.

[0026] Preferably, the grafting agent is any one of 1,7,7-trimethylbicyclo[2.2.1]hept-2-yl methacrylate, isobornyl methacrylate, and 3-isobornylcyclohexyl acrylate.

[0027] Preferably, the filler is any one of glass fiber, graphite, carbon fiber, talcum powder and silicon dioxide.

[0028] Preferably, the stirring time for the blue light to appear in step S4 is 20-60 min.

[0029] Preferably, in step S5, the pH is adjusted to 7-8 with aqueous ammonia.

[0030] The invention also discloses the application of the corrosion-resistant polytetrafluoroethylene pipe in the fields of chemical industry, petroleum and natural gas.

[0031] In this recipe, the ingredients and their functions are as follows:

[0032] The role of the modifier is to improve and enhance the performance of polytetrafluoroethylene, making it more suitable for specific application requirements. The modifier can improve the mechanical strength, heat resistance, chemical resistance, dynamic friction coefficient and compatibility with other materials of polytetrafluoroethylene. By introducing specific quaternary ammonium salt groups, the modifier can give polytetrafluoroethylene tube composite materials new functional properties such as antibacterial properties. The modifier contains double bonds and ester groups that can react with the grafting agent to introduce the functional functional groups in the grafting agent to the modifier, and the modifier is then modified with the flexible monomer, and the obtained product is reacted with the rigid monomer to obtain a modified acrylate copolymer.

[0033] The flexible monomer can interact with the rigid monomer and the functional monomer in the preparation process of the modified acrylate copolymer to form a cross-linked network, thereby improving the mechanical strength and durability of the composite material. In addition, the flexible monomer can also improve the processing properties of the composite material, making it easier to extrude and shape.

[0034] The rigid monomers can interact with the flexible monomers and the functional monomers during the preparation of the modified acrylate copolymers to form a cross-linked network, thereby improving the mechanical strength and durability of the composite materials.

[0035] Grafting agents such as isobornyl methacrylate, 3-isobornyl cyclohexyl acrylate, etc., these double bonds can undergo copolymerization or grafting reactions with the active groups in the modifier. The double bonds of the grafting agent can be attacked by free radicals initiated by ammonium persulfate to form active free radical points, which can further react with the monomers in the modifier, thereby introducing new side chains or functional groups on the main chain of the polytetrafluoroethylene polymer.

[0036] Beneficial effects of the present invention:

[0037] Compared with the prior art, a modified acrylate copolymer is prepared by cross-linking a flexible monomer, a rigid monomer, a modifier and a grafting agent, and the quaternary ammonium salt group carried by the modifier and the ring structure carried by the grafting monomer can make the prepared modified acrylate have antibacterial properties and good mechanical properties. The modified acrylate copolymer is then blended with other raw materials such as polytetrafluoroethylene materials to prepare a composite material, so that the composite material has excellent mechanical properties, a low friction coefficient and good antibacterial effects, and extends the service life of the polytetrafluoroethylene pipe. DETAILED DESCRIPTION

[0038] The parameters and sources of some substances in the examples are as follows:

[0039] (3-Hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate, CAS: 13052-11-4.

[0040] 1,7,7-triMethylbicyclo[2.2.1]hept-2-yl methacrylate, 2-Methyl-2-Propenoic acid-1,7,7-triMethylbicyclo[2.2.1]hept-2-yl ester, CAS No.: 16868-12-5.

[0041] Diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, 2-(2-[4-(1,1,3,3-Tetramethylbutyl)phenoxy]ethoxy)ethanol, CAS No.: 9036-19-5.

[0042] Theaflavin-3-gallate, CAS number: 30462-34-1.

[0043] Polytetrafluoroethylene, brand: 850A, DuPont Company, USA.

[0044] Glass fiber, brand: T436, fiber diameter 11μm, short cut length 3.0mm, Taishan Glass Fiber Co., Ltd.

[0045] Ammonium perfluorooctanoate, CAS number: 3825-26-1.

[0046] Antibacterial agent, model: zeomic DLD502, Japan Zeomic.

[0047] Example 1

[0048] A method for preparing a corrosion-resistant polytetrafluoroethylene pipe comprises the following steps, measured in parts by weight:

[0049] Step 1: 50 kg of polytetrafluoroethylene, 2 kg of ammonium perfluorooctanoate, 15 kg of glass fiber, 1 kg of antibacterial agent, 2 kg of 3-(isobutyleneoxy)propyltrimethoxysilane and 12 kg of modified acrylate copolymer are mixed evenly, mixed with a high-speed mixer for 35 minutes, and then extruded through an extruder, molded at a pressure of 30 MPa, and maintained at pressure for 12 minutes to obtain a molded product;

[0050] Step 2: Place the formed product in a high-temperature sintering furnace, heat it from 25°C to 370°C at a heating rate of 30°C / hour, keep it at 370°C for 30 minutes, obtain the sintered product and cool it at 25°C to obtain the polytetrafluoroethylene pipe.

[0051] Wherein, the preparation method of the modified acrylate copolymer comprises the following steps:

[0052] S1. Mix 10 kg of diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, 3 kg of sodium carbonate, 15 kg of (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate, 6 kg of octadecyl acrylate, 6 kg of theaflavin-3-gallate and 15 kg of 3-isobornylcyclohexyl acrylate, and stir at 500 rpm for 20 min to obtain a monomer mixture. Divide the monomer mixture into two equal portions for standby use, each portion weighing 27.5 kg;

[0053] S2, 40L of water, 5kg of diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, and 3kg of sodium carbonate were added to the reaction kettle in sequence, stirred at 500rpm for 25min, and then 27.5kg of the monomer mixture prepared in step S1 was added, and stirring was continued for 45min to obtain a pre-emulsion;

[0054] S3, dissolve 5kg of ammonium persulfate in 20L of water to obtain an ammonium persulfate aqueous solution for standby use;

[0055] S4, add 25L of water to the remaining 27.5kg of the monomer mixture prepared in step S1, raise the temperature to 70°C, add 20kg of the pre-emulsion prepared in step S2 and 6kg of the ammonium persulfate aqueous solution prepared in step S3, raise the temperature to 95°C and keep the temperature unchanged, continue to stir at 500rpm, and continue to stir for 35min after obvious blue light appears to obtain a seed emulsion;

[0056] S5. Continue to add the remaining pre-emulsion and aqueous ammonium persulfate solution to the seed emulsion prepared in step S4 within 3 hours, keep warm at 90° C. for 2 hours, then cool to 35° C., adjust the pH to 8 with aqueous ammonia, cool to 25° C., filter to obtain a residue, dry at 50° C. for 10 hours, and cool to obtain a modified acrylate copolymer.

[0057] Example 2

[0058] The difference between Example 2 of the present application and Example 1 is that the (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate in Example 1 is replaced by 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester.

[0059] Example 3

[0060] The difference between Example 3 of the present application and Example 1 is that the (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate in Example 1 is replaced by di(2-methyl-2-propenoic acid) 2-hydroxy-1,3-propylene glycol ester.

[0061] Example 4

[0062] The difference between Example 4 of the present application and Example 1 is that the 3-isobornylcyclohexyl acrylate in Example 1 is replaced by 1,7,7-trimethylbicyclo[2.2.1]hept-2-yl methacrylate.

[0063] Example 5

[0064] The difference between Example 5 of the present application and Example 1 is that the 3-isobornylcyclohexyl acrylate in Example 1 is replaced by isobornyl methacrylate.

[0065] Comparative Example 1

[0066] The difference between Comparative Example 1 of the present application and Example 1 is that the (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate in Example 1 is replaced by β-hydroxypropyl methacrylate.

[0067] Comparative Example 2

[0068] The difference between Comparative Example 2 of the present application and Example 1 is that the 3-isobornylcyclohexyl acrylate in Example 1 is replaced by isobornyl acrylate.

[0069] Test Example 1

[0070] Dynamic friction coefficient test: Take the polytetrafluoroethylene pipes prepared in Examples 1-5 and Comparative Examples 1-2, and test the dynamic friction coefficient of the polytetrafluoroethylene pipe according to the test method in GB / T3960-2016 "Plastic Sliding Friction and Wear Test Method". The test conditions are: 196V, 0.42m / s×60min. The test results are shown in Table 1:

[0071] Antibacterial performance: The antibacterial ability of the pipes obtained in Examples 1-5 and Comparative Examples 1-2 was tested according to the test method of GB / T 31402-2023 "Determination of antibacterial activity on the surface of plastics and other non-porous materials". The test results are shown in Table 1:

[0072] Table 1 Heat resistance test

[0073] Experimental groups Dynamic friction coefficient Anti-E. coli efficiency / % Anti-Staphylococcus aureus efficiency / % Example 1 0.14 99.5 99.8 Example 2 0.19 85.2 84.8 Example 3 0.18 82.5 81.6 Example 4 0.20 98.4 98.8 Example 5 0.18 97.6 97.3 Comparative Example 1 0.26 78.5 76.5 Comparative Example 2 0.25 97.6 97.1

[0074] Note: Escherichia coli is a commercial product, CGMCC 1.2463; Staphylococcus aureus is a commercial product, CGMCC1.2910.

[0075] Test Example 2

[0076] According to GB / T 1447-2005 "Test Method for Tensile Properties of Fiber Reinforced Plastics", GB / T1040.1-2018 "Determination of Tensile Properties of Plastics Part 1: General Principles" and QB / T4877-2015 "Polytetrafluoroethylene Tubes", the polytetrafluoroethylene tubes prepared in Examples 1-5 and Comparative Examples 1-2 were tested, and the test results are shown in Table 2:

[0077] Table 2 Mechanical properties test

[0078]

[0079]

[0080] The dynamic friction coefficient is a key indicator for evaluating the friction characteristics of PTFE tubing. By testing it, we can predict the friction resistance encountered by PTFE tubing during movement or transportation, and then determine its suitability in different application scenarios. The low friction of PTFE tubing helps to reduce wear on the contact surface, thereby extending its service life. Therefore, the dynamic friction coefficient is not only directly related to the friction performance of PTFE tubing, but also has a significant impact on its durability and maintenance costs. Therefore, the level of dynamic friction coefficient directly affects the efficiency and durability of PTFE tubing in practical applications.

[0081] Through the test data in Table 1 and Table 2, it can be found that compared with Examples 1-5 and Comparative Examples 1-2, the polytetrafluoroethylene tube prepared in Example 1 has good antibacterial properties, mechanical properties, and low friction properties, thereby extending the service life of the polytetrafluoroethylene tube composite material.

[0082] Compared with the data in the table of Examples 1-3 and Comparative Example 1, it is found that each data has differences, and the reason for these differences may be that different modifiers are used. The modified acrylate copolymer prepared indirectly affects the physical and chemical properties of polytetrafluoroethylene tubing because of the different functional groups carried by the modifier and the grafting agent. Compared with the modifiers in Examples 1-3 and Comparative Example 1, the modifier in Example 1, in addition to having the same double bonds and ester functional groups participating in the reaction as the modifiers in Examples 2-3 and Comparative Example 1, also belongs to quaternary ammonium salt. (3-hydroxypropyl) trimethylammonium chloride-2-hydroxy crotonate belongs to quaternary ammonium salt, and quaternary ammonium salt molecules can exist on the surface or inside of polytetrafluoroethylene tubing as a way to prepare polytetrafluoroethylene tubing raw materials, thereby forming a layer of antibacterial barrier, preventing bacteria from attaching and growing, on the other hand, the quaternary ammonium salt contained and the antibacterial property act synergistically, and have good antibacterial properties in polytetrafluoroethylene tubing. The modifiers in Examples 2-3 and Comparative Example 1 only have double bonds and ester groups involved in preparing modified acrylate copolymers and are not quaternary ammonium salts. Therefore, the antibacterial property of the polytetrafluoroethylene tube composite material prepared in Example 1 is the best.

[0083] Comparing the data of Example 1, Examples 4-5 and Comparative Example 2, it can be found that each data is different, and the reason for these differences may be that different grafting agents are used. The grafting agent contains double bonds that can undergo addition reactions with the modifier, and the functional groups carried are grafted onto the modifier, thereby changing the physical and chemical properties of the modified acrylic acid. Compared with the grafting agents in Example 1, Examples 4-5 and Comparative Example 2, the grafting agent in Example 1 contains a cyclic structure in addition to double bonds. The cyclic structure limits the linear motion of the polymer chain and reduces the freedom of motion of the chain segment. In turn, the glass transition temperature of the material can be increased; at the same time, the cyclic structure may provide more intermolecular action sites, and the van der Waals force can enhance the interaction between polymer chains, thereby improving the mechanical strength and toughness of the polytetrafluoroethylene tube.

[0084] At the same time, because the cross-linking density of the polytetrafluoroethylene pipe prepared in Example 1 is high, it has better deformation and low friction coefficient, which may reduce the dynamic friction coefficient of the polytetrafluoroethylene pipe. In Example 1, functional groups such as double bonds, ester groups, quaternary ammonium salt groups and cyclic structures are introduced in the preparation process of the polytetrafluoroethylene pipe, and these functional groups, as cross-linking active sites, significantly increase the cross-linking density of the material. Cross-linking density refers to the degree to which molecular chains in polymer materials are interconnected by chemical bonds. High cross-linking density means that more chemical bonds are formed between molecular chains, thereby enhancing the overall structural stability and mechanical strength of the material. This enhanced structural stability gives the polytetrafluoroethylene pipe better deformation resistance and low dynamic friction coefficient, so that when it is rubbed, it can maintain the stability of shape and size and is not easy to deform. Due to the increase of cross-linking active sites, a more compact three-dimensional network structure is formed between the molecular chains of the polytetrafluoroethylene pipe, which not only enhances the cohesive force of the material, but also makes the surface of the material smoother, and the reduction of surface roughness is directly related to the friction behavior of the material when it contacts with other objects. During the friction process, lower surface roughness means fewer microscopic protrusions and depressions, and these microstructures are the main source of friction. Therefore, the reduction of surface roughness helps to reduce the friction contact points, thereby reducing the dynamic friction coefficient. However, in Examples 4-5 and Comparative Example 2, because the crosslinking density of the polytetrafluoroethylene tube is low, the dynamic friction performance is worse.

Claims

1. A corrosion-resistant polytetrafluoroethylene pipe, characterized in that: The method for preparing the corrosion-resistant polytetrafluoroethylene pipe comprises the following steps, measured in parts by weight: Step 1, 30-50 parts of polytetrafluoroethylene, 2-5 parts of perfluorocarboxylate, 0.5-1 parts of antibacterial agent, 5-20 parts of filler, 1-4 parts of coupling agent and 5-20 parts of modified acrylate copolymer are mixed evenly, and extruded to obtain a molded product; Step 2: sintering the formed product at 310-390° C., cooling the sintered product at room temperature, and obtaining a polytetrafluoroethylene tube; The preparation method of the modified acrylate copolymer comprises the following steps: S1, diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, alkaline regulator, modifier, flexible monomer, rigid monomer and grafting agent are uniformly mixed to obtain a monomer mixture, and the monomer mixture is evenly divided into two equal parts for standby use; S2, separately stirring water, diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether and alkaline regulator at a constant temperature, then adding one portion of the monomer mixture prepared in step S1, and continuing stirring for 10-50 minutes to obtain a pre-emulsion; S3, dissolving ammonium persulfate in water to obtain an ammonium persulfate aqueous solution for standby use; S4, adding water to the remaining monomer mixture prepared in step S1, heating to 60-80° C., adding 1 / 4-1 / 2 of the pre-emulsion prepared in step S2 and 1 / 4-1 / 2 of the ammonium persulfate aqueous solution prepared in step S3, raising the temperature to 85-100° C. and maintaining the temperature unchanged, continuing to stir, and continuing to stir after obvious blue light appears to obtain a seed emulsion; S5. Continue to add the remaining pre-emulsion and aqueous ammonium persulfate solution to the seed emulsion prepared in step S4 within 2-5 hours, keep warm at 85-100° C. for 1-4 hours, then cool to 30-55° C., adjust the pH with aqueous ammonia, cool to room temperature, filter, dry, and cool to obtain a modified acrylate copolymer.

2. The corrosion-resistant polytetrafluoroethylene pipe according to claim 1, characterized in that: The preparation method of the modified acrylate copolymer comprises the following steps, calculated in parts by weight: S1. Evenly mix 4-15 parts of diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, 2-8 parts of alkaline regulator, 3-15 parts of modifier, 5-14 parts of flexible monomer, 3-16 parts of rigid monomer and 3-15 parts of grafting agent to obtain a monomer mixture, and divide the monomer mixture into two equal parts for standby use; S2, 10-50 parts of water, 2-13 parts of diethylene glycol mono[(1,1,3,3-tetramethylbutyl)phenyl]ether, and 2-8 parts of sodium carbonate are stirred at a constant temperature, and then one part of the monomer mixture prepared in step S1 is added, and stirring is continued for 20-50 minutes to obtain a pre-emulsion; S3, dissolving 2-8 parts of ammonium persulfate in water to obtain an ammonium persulfate aqueous solution for standby use; S4, adding 10-50 parts of water to the remaining monomer mixture prepared in step S1, heating to 60-80° C., adding 1 / 4-1 / 2 of the pre-emulsion prepared in step S2 and 1 / 4-1 / 2 of the ammonium persulfate aqueous solution prepared in step S3, raising the temperature to 85-100° C. and maintaining the temperature unchanged, continuing to stir, and continuing to stir after obvious blue light appears to obtain a seed emulsion; S5. Continue to add the remaining pre-emulsion and aqueous ammonium persulfate solution to the seed emulsion prepared in step S4 within 2-5 hours, keep warm at 85-100° C. for 1-4 hours, then cool to 30-55° C., adjust the pH with aqueous ammonia, cool to room temperature, filter, dry, and cool to obtain a modified acrylate copolymer.

3. The corrosion-resistant polytetrafluoroethylene pipe according to claim 1, characterized in that: The modifier is any one of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester, di(2-methyl-2-acrylic acid) 2-hydroxy-1,3-propylene glycol ester, and (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate.

4. The corrosion-resistant polytetrafluoroethylene pipe according to claim 3, characterized in that: The modifier is (3-hydroxypropyl)trimethylammonium chloride-2-hydroxycrotonate.

5. The corrosion-resistant polytetrafluoroethylene pipe according to claim 1 or 2, characterized in that: The flexible monomer is octadecyl acrylate; the rigid monomer is theaflavin-3-gallate.

6. The corrosion-resistant polytetrafluoroethylene pipe according to claim 1 or 2, characterized in that: The grafting agent is any one of 1,7,7-trimethylbicyclo[2.2.1]hept-2-yl methacrylate, isobornyl methacrylate, and 3-isobornylcyclohexyl acrylate.

7. The corrosion-resistant polytetrafluoroethylene pipe according to claim 1, characterized in that: The filler is any one of glass fiber, graphite, carbon fiber, talcum powder and silicon dioxide.

8. The corrosion-resistant polytetrafluoroethylene pipe according to claim 1 or 2, characterized in that: The stirring time for the blue light to appear in step S4 is 20-60 minutes.

9. The corrosion-resistant polytetrafluoroethylene pipe according to claim 1 or 2, characterized in that: In step S5, the pH is adjusted to 7-8 with aqueous ammonia.

10. Use of the corrosion-resistant polytetrafluoroethylene pipe according to any one of claims 1 to 9 in the fields of chemical industry, petroleum and natural gas.

Citation Information

Patent Citations

  • Polytetrafluoroethylene pipe and preparation method thereof

    CN113354913A

  • Modified polytetrafluoroethylene mold-pressed pipe and preparation method thereof

    CN113416369A